Attack of the jack-o'-lanterns - Stine, R. L. (New York : Scholastic Inc., 1996)
A practical joke involving two scary pumpkin heads turns into a Halloween night of terror when the pumpkins develop strange hissing voices and flames shoot out of their faces.
Drew and Walker plan some halloween revenge involving two scary pumpkin heads.
"An Apple paperback."
"A Parachute Press book."
480
RL4.
008-012.
Accelerated Reader AR
Keywords: Halloween -- Juvenile fiction; Jack-o-lanterns -- Juvenile fiction; Horror tales